IMPLEMENTATION OF NEWMAN NETWORK PARTITIONING ALGORITHM BY CONSIDERING DEGREE OF CORRELATION IN URBAN TRAFFIC NETWORKS - Farhanulhakim, M.
The rapid population growth and urbanization in Indonesia, along with the increasing number of motor vehicles, have made traffic congestion a serious problem in major cities. One strategy to address this issue is the implementation of coordinated traffic control systems. However, the high complexity of urban traffic networks necessitates network partitioning before implementing such control systems. This study aims to partition the traffic network in Jakarta using the Newman algorithm, considering correlation degree. The correlation degree represents the strength of the relationship between intersections based on static characteristics (such as road length and number of lanes) and dynamic characteristics (such as vehicle flow and maximum average queue length in a lane at a specific time interval). This approach allows the grouping of intersections with similar traffic characteristics, resulting in sub-networks with more homogeneous traffic information. The condition of the sub-networks is analyzed using the Macroscopic Fundamental Diagram (MFD) to ensure traffic information homogeneity and to determine the maximum average vehicle flow and critical traffic density as inputs for the control system. The results show that the optimal partitioning for Jakarta's traffic occurs when the network with 31 intersections is divided into 3 sub-networks. The homogeneity of traffic information in each sub-network is confirmed by the well-defined MFD, demonstrating the success of the applied partitioning method. Keywords: Coordinated Traffic Control System, Traffic Network Partitioning, Degree of Correlation, Macroscopic Fundamental Diagram.